137. Applying Gamification to Microbiology Core Curriculum in Undergraduate Medical Education. (31st December 2020) - Walker, Jeremey; Patel, Mukesh; Cleveland, John D; Heudebert, Jose Pablo; Westfall, Andrew O; Dempsey, Donald; Guzman, Alfredo; Long, Dustin; Willig, James; Lee, Rachael A
Abstract: Background: Gamification uses elements of game design to enhance learner engagement. We introduced a microbiology "trivia game" for first year medical students (MS1), leveraging principles of gamification (self-efficacy, points, leaderboards, etc.) to enhance participation. We hypothesized this would engage learners and improve course performance. Methods: We created a "microbiology trivia game" using Kaizen-Education, a software platform (Kaizen) developed by our Center for Clinical and Translational Science. All MS1 in the Microbiology course at the University of Alabama at Birmingham (Fall 2019) were invited to participate by downloading the smartphone app. We created 56 questions emphasizing high yield concepts and their clinical application. Participation was voluntary during the Microbiology course (3 weeks). We collected app utilization and test performance data in this IRB approved investigation. We completed descriptive analyses of student engagement including a Player Efficiency Rating (PER). The PER is a student-level composite measure of student accuracy, play frequency and question completion. We calculated Spearman rank correlation of mean exam scores and PER. At course completion students received a survey about their experience. Results: 181 (96%) of 189 Microbiology students answered ≥ 1 question. Across those 181 students, 161 (89%) completed all questions (table 1). An average of 67 students answered questions each day. Collectively, students answered 96% of all published questions (n=10, 136; 56 questions x 181 students). A total of 49% of questions were answered < 24H from publication. Survey response rate was 34% (n=61), and our teaching innovation was positively received (table 2). Final exam performance increased from 80% (2018) to 87% (2019) among students in the gamification enhanced Microbiology course. A correlation between higher PER and better exam scores was found (0.34; p≤0.0001). Conclusion: Our gamification infused Microbiology course was well received. Students appreciated the opportunity to apply core foundational microbiology concepts to clinical medicine scenarios early in training. Novel teaching methods may increase student engagement in Medical Microbiology courses, for many the birthplace of their passion for Infectious Diseases. Disclosures: All Authors : No reported disclosures